Approaches to Craft Studies at Higher Education - Kokko, Sirpa (FormAkademisk, 2021)
The purpose of this article is to explore the various approaches to craft studies at higher education institutions. Based on fieldwork observations and document analysis of the curricula of four European and one US university craft study programmes, similarities and differences were found. The similarities concerned the pedagogy to acquire basic skills and the urge to keep up craft traditions. The differences concerned the broader aims of study and the students’ prospective career paths. The following approaches to craft studies in higher education were detected: 1. Educational crafts, 2. Traditional crafts, 3. Critical crafts, 4. Cultural heritage of crafts, and 5. Design-based crafts.